Curriculum Analysis Of The Character Education System In Indonesia And Finland - Mumu Muzayyin Maq; Nasril Nasril; Oktosiyanti Oktosiyanti; Akhmad Ramli; Bernardus Agus Rukiyanto (PT. Banjarese Pacific Indonesia, 2025)
This research aims to analyze the comparison of character education system curricula in Indonesia and Finland. The focus of the research is to identify differences and similarities in the approach, implementation and effectiveness of character education in the two education systems. The research method used is a literature study with a qualitative approach. Data was collected through reviewing curriculum documents, education policies, and scientific articles related to character education in Indonesia and Finland. The research results show that Finland integrates character education holistically in all aspects of learning, while Indonesia still tends to separate character education as a separate subject. Apart from that, Finland emphasizes the formation of values ​​of independence, responsibility and collaboration through a student-centered approach, while Indonesia places more emphasis on religious values ​​and nationalism. The implication of this research is the need to reorient the character education curriculum in Indonesia to better integrate character values ​​in the entire learning process, as well as adopting best practices from Finland which have been proven effective in shaping students' character.